PENGELOLAAN HARTA ZAKAT PERSPEKTIF HUKUM DAN DAMPAKNYA PADA SOSIO-EKONOMI MASYARAKAT (Studi pada Lembaga Amil Zakat Masjid dan Musholla Se-Bandar Lampung) - AS, Susiadi; Putra, Andi Eka (Universitas Islam Negeri Raden Intan Lampung, 2020)
Management of zakat in Indonesia has two types of institutions, namely the Amil Zakat Agency (BAZ) and the Amil Zakat Institution (LAZ). By definition, the Zakat Management Institution (LPZ) is an institution tasked with managing zakat, infaq, and shadaqah, both formed by the government such as BAZ, as well as those formed by the public and protected by the government such as LAZ. That